Infecção hospitalar associada ao uso de cateter venoso central e a quebra de protocolos pelos profissionais de saúde na UTI de um hospital universitário em Natal/RN - Barreto, Analucia Filgueira Gouveia (2010)
This is a study descriptive cross-sectional and quantitative approaches, which aimed to analyze the association between hospital infection rate for insertion, maintenance of central venous catheter and the breakdown of protocols (rules and routines) by health professionals assisting patients in the ICU of a university hospital in Natal / RN. The process of data collection was through observation with structured form, refers to medical records and structured questionnaires with health professionals. The results were organized, tabulated, categorized and analyzed using SPSS 14.0. The characterization of the subjects was performed using descriptive and inferential statistics, taking into account the nature of the variables, with analysis of variance (ANOVA) and Spearman correlation test, it was a discussion of the information obtained, considering the mean, standard deviation, coefficient of variance and standard error. The variables that showed a higher level of correlation were treated with the application of significance tests. As the results, 71% of participants were female and 29% male, age ranged from 18 to 85 years (52.6 ± 22.5). The insertion, there was a variation from 0 to 5 errors (1.2 ± 1.4), during maintenance, the average was 2.3 ± 0.9 errors, ranging from 0 to 4. During the insertion and maintenance of CVC, patients who had been an infection ranging from 2 to 9 mistakes (4.2 ± 1.7), since those who did not show the variation goes from 0 to 5 errors (2, 8 ± 1.5). The correlation coefficient between the risk of infection throughout the process and the risk of infection at the insertion showed strong and significant (r = 0.845 p = 0.000) and in relation to risk of infection in maintenance was moderate and significant (r = 0.551 p = 0.001). The mistakes made by professionals in the procedures for insertion and maintenance of the catheter, associated with other conditions, shown as a risk factor for the of IH